Evaluation of Physicochemical, Functional, and Sensorial Characteristics of Gluten-Free Turkish Noodle “Erişte” Formulated with Oat and Quinoa Flours - Gülşah Çalışkan Koç; Ravi Pandiselvam (Journal of Food Quality)
This study aimed to develop and characterize the new gluten-free erişte formulated by using oat flour (100%), quinoa flour (100%), and oat + quinoa flour blend (50% + 50% by weight). The physicochemical, functional, and sensorial properties of developed gluten-free eriştes were evaluated. The moisture content values of gluten-free erişte samples were lower than 12% wet basis (w.b.). The highest ash (3.74 ± 0.63%), fat (8.17 ± 0.19%), and protein (18.74 ± 0.41%) content values were obtained for quinoa flour erişte. The highest water (76.67 ± 9.07%) and oil holding capacity (49.50 ± 7.78%) values were observed for quinoa flour erişte and oat + quinoa flour erişte samples, respectively. The highest brightness (L∗) value was observed for oat + quinoa flour erişte (p<0.05). The quinoa flour erişte sample has the highest weight (354.22 ± 20.14%) and volume (268.20 ± 9.01%) increase values. The lowest (10.56 ± 1.83%) and highest (13.71 ± 0.83%) cooking loss values were observed from oat flour and quinoa flour erişte samples, respectively. In the light of the findings, it can be concluded that both oat and quinoa flours and their mixtures can be used to make gluten-free erişte, and the erişte samples were liked by the panelists.